2017
DOI: 10.1016/j.jtusci.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel spectrophotometric method for the determination of copper ion by using a salophen ligand, N,N′-disalicylidene-2,3-diaminopyridine

Abstract: In this study, a novel, selective and highly sensitive spectrophotometric method has been developed for the determination of copper(II) by using a new chromogenic reagent N,N-bissalicylidene-2,3-diaminopyridine (H 2 IF). The absorbance was measured at max = 414 nm. Experimental conditions were optimized, and Beer's law was observed in the concentration range of 6.35-318 g L −1 of copper. The molar absorptivity of the complex was calculated and found to be 1.46 × 10 5 L mol −1 cm −1. The detection and quantific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The spectrophotometric method developed within the scope of the study seems to be more advantageous in terms of the short duration of the reaction period than other existing methods [13][14][15][16][17][18][19][20]. Experimental findings have shown that in aqueous media the reagent is a potential application for the sensitive, rapid and selective perception of Cu (II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrophotometric method developed within the scope of the study seems to be more advantageous in terms of the short duration of the reaction period than other existing methods [13][14][15][16][17][18][19][20]. Experimental findings have shown that in aqueous media the reagent is a potential application for the sensitive, rapid and selective perception of Cu (II).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, a relevant benchmark of spectrophotometric methods from the attached literature [13][14][15][16][17][18][19][20] and from present study is compiled and given in Table 3. All parameters in Table 3 are nearly comparable within a reasonable data range and seem not superior to each other in general trend.…”
Section: Comparison With the Current Literaturementioning
confidence: 99%
“…Standard addition method is used to determine copper content even at low concentration and to avoid effect of matrix in different samples. The resulted values and their statistical treatment are showed in figures (10)(11)(12)(13)(14)(15) and table 10 below: Un acceptable error at concentration 500 ppm and less despite of presence of oxalate ions. Figure 11: standard addition curve for Cu 2+ determination in tap water.…”
Section: 6-the Applicationsmentioning
confidence: 99%
“…Considering the toxic effects of copper, its determination is quite critical. There are a number of analytical techniques that have been reported for the determination of copper ions at very low concentration levels, including ion chromatography [7,8], UV-Vis Spectrophotometry [9,10], flame atomic absorption spectrometry (FAAS) [11,12], graphite-furnace atomic absorption spectrometry (GF AAS) [13], Colorimetry [14][15][16], fluorescence spectroscopy [17,18], ICP-MS [19], ICP-OES [20], ICP-AES [21], Capilarry Electrophoresis-UV [22], titrimetry [23], gravimetry [24], electrogravimetry [25] and electrochemical methods [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%